The Role of Social Competence of Islamic Education Teachers in the Formation of Student Character at MAN 1 Mojokerto - Nurul Fadilah; Zahwa Machrun Nisa; Wiwin Luqna Hunaida (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2025)
This study examines the influence of Islamic Education (PAI) teachers’ social competence on the character development of students at MAN 1 Mojokerto. Data were collected through observation, in-depth interviews with PAI teachers, and document analysis using a qualitative approach. The findings indicate that teachers play a significant role in shaping students' character through effective communication skills, fostering positive social relationships, and demonstrating exemplary behavior. Strategies employed include role modeling, collaborative learning such as discussions on "The Exemplary Companions of the Prophet," and collaboration with parents through parenting seminars. Identified challenges include the negative impact of digital technology, lack of parental supervision, and the critical nature of Generation Z students. Supporting factors involve the active roles of both teachers and families, while inhibiting factors include disharmonious family environments, students’ innate character traits, and technological influences. The study concludes that enhancing teachers’ social competence, fostering school–parent synergy, and adapting to digital era challenges are vital for successful character education.